2011
DOI: 10.1177/0883073810395391
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A on Oral Health in Treating Sialorrhea in Children With Cerebral Palsy: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Intrasalivary gland injection of botulinum toxin type A is known to treat sialorrhea effectively in children with cerebral palsy. However, oral health may be compromised with escalating dose. In this randomized, double-blind, and placebo-controlled pilot trial, the authors aim to determine the therapeutic effect of low-dose, ultrasonography-controlled botulinum toxin type A injection to bilateral parotid and submandibular glands on oral health in the management of sialorrhea. Twenty children diagnosed with cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 27 publications
1
32
1
5
Order By: Relevance
“…In this study, objective results showed significant reduction in drooling after injections, but the subjective scales did not show the same effect. Correlation between objective and subjective responses was not assessed statistically (Wu et al, 2011). On the whole, these studies demonstrate that a combination of objective and subjective scales is useful to assess drooling reduction accurately.…”
Section: Wu Et Al Evaluated Botulinum Toxin-a Injections On Droolingmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, objective results showed significant reduction in drooling after injections, but the subjective scales did not show the same effect. Correlation between objective and subjective responses was not assessed statistically (Wu et al, 2011). On the whole, these studies demonstrate that a combination of objective and subjective scales is useful to assess drooling reduction accurately.…”
Section: Wu Et Al Evaluated Botulinum Toxin-a Injections On Droolingmentioning
confidence: 84%
“…Most of the studies reported drooling improvement on subjective and objective methods, but no statistical assessment was performed in order to find the relationship between the subjective and objective scales. Four studies however did not find an agreement in the subjective and objective responses (Jeung et al, 2012;Lin et al, 2008;Nordgarden et al, 2012;Wu et al, 2011). Thus, it is difficult to conclude that drooling reduction was assessed accurately.…”
Section: Wu Et Al Evaluated Botulinum Toxin-a Injections On Droolingmentioning
confidence: 89%
“…A lack of correlation between reduction in salivary secretion and improvement in drooling has been observed in some studies and is probably related to the fact that factors influencing the severity of drooling and reduction of saliva secretion are variable [51]. …”
Section: Commentary On Studiesmentioning
confidence: 99%
“…367 papers identified 232 papers identified 1 Cochrane protocol identified 18 9 literature reviews; no systematic review with meta-analysis 12,35,[41][42][43][44][45][46][47] 26 papers reviewed for content 135 duplicates deleted 190 papers deleted on basis of title and abstract 5 randomized controlled trials 17-21 and 11 prospective studies [22][23][24][25][26][27][28][29][30][31] with usable information by outcome and included in meta-analysis 5 case studies (n≤4) and retrospective reviews discarded [48][49][50][51][52] 1 study discarded: no patients with cerebral palsy 53 6 papers discarded owing to lack of available quantitative data to be incorporated in meta-analysis. 10,11,[54][55][56][57] 3 studies discarded as they had injections of botulinum toxin with ≤3 monthly intervals [58][59][60] 1 study excluded as it included adult patients up to age 74 years 61 Figure 1: Included and excluded studies.…”
Section: Description Of Studiesmentioning
confidence: 99%